Individual and Province-level Determinants of Unemployed NEET as Young People’s Productivity Indicator in Indonesia During 2020: A Multilevel Analysis Approach - Ni Putu Gita Naraswati; Yogo Aryo Jatmiko (Politeknik Statistika STIS, 2021)
Nowadays, employment has become one of the focus of attention for developing countries, including Indonesia. This is one of the urgencies that must be addressed considering that the Indonesian population is entering the demographic divident period. Success in achieving the demographic divident is very dependent on the employment conditions of young people in realizing a low level of dependence. However, obstacles in terms of education and employment are still experienced by youth which can be seen from the percentage of NEET from Year-on-Year (YoY), especially in 2020 it is exacerbated by Covid-19 pandemic. Based on these problems, it is necessary to research NEET in Indonesia in 2020. This study uses 2020 National Labor Force Survey (Sakernas) data which is analyzed by using multilevel binary logistic regression analysis. The unemployed status of young NEETs is influenced by gender, age, marital status, highest education completed, disability status, classification of the area of residence, and recent migrant status. There is a multilevel effect in the NEET assessment of young people as evidenced by the influence of Gross Domestic Product (GDP) and Human Development Index (HDI). The research results are expected to be used as a reference in making policies to optimizing the mismatch program on the pre-employment card to bridge the young age of job seekers with available job opportunities and based on the province-level variable, the province government are expected to maximize the province-level variables that affect the tendency of NEETs to remain active in the labor market. that are targeted towards the NEET problem in Indonesia.